A STUDY ON EMPLOYEES’ ATTITUDES TOWARDS THE ORGANIZATION - Siddique, Dr. R. Mohammed Abubakkar; Indira, Dr. N. (The journal of contemporary issues in business and government, 2020)
The analysis has been made mainly based on the primary data that is by the employee’s opinion. For this a sample size of 110 was taken and the simple random sampling method has been used to select the samples from the total population. The study provides the opinion of employees about all the H.R functions of Volgga Waters Pvt Limited. The causes of employee attitudes, the results of positive or negative job satisfaction, and how to measure and influence employee attitudes, employee conditions, salary range and incentives, work performance etc. Reliability test is used to reveal that acceptable of this study, Chi Square is used to reveal that there was no association between the gender of the employees and the work stress. Correlation is used to reveal that there was no significant correlation between the salary range and satisfaction level of salary and F test is used to reveal that there was no significant the age and the type of work performed by the employees